Ultrasound‐Triggered Delivery of Anticancer Therapeutics from MRI‐Visible Multilayer Microcapsules. Issue 5 (3rd July 2018) - Alford, Aaron; Rich, Megan; Kozlovskaya, Veronika; Chen, Jun; Sherwood, Jennifer; Bolding, Mark; Warram, Jason; Bao, Yuping; Kharlampieva, Eugenia
Abstract: Although imaging‐guided drug delivery represents a noninvasive alternative to both surgical resection and systemic methods, it has seen limited clinical use due to the potential toxicity and fast clearance of currently available imaging agents. Herein, we introduce theranostic biocompatible microcapsules as efficient contrast‐enhanced imaging agents that combine magnetic resonance imaging (MRI) with ultrasound‐triggered drug release for real‐time tracking and targeted delivery in vivo. The 3‐μm diameter capsules are assembled via layer‐by‐layer deposition of the natural polyphenol tannic acid and poly( N ‐vinylpyrrolidone) with 4 nm iron oxide nanoparticles incorporated in the capsule wall. The nanoparticle‐modified capsules exhibit excellent T1 and T2 MRI contrast in a clinical 3T MRI scanner. Loaded with the anticancer drug doxorubicin, these capsules circulate in the blood stream for at least 48 h, which is a remarkable improvement compared to nonencapsulated nanoparticles. The application of focused ultrasound results in targeted drug release with a 16‐fold increase in doxorubicin localization in tumors compared to off‐target organs in a mouse model of breast cancer. Owing to the active contrast, long circulation, customizable size, shape, composition, and precise delivery of high payload concentrations, these materials present a powerful and safe platform for imaging‐guided precision drug delivery. Abstract : Theranostic biocompatible microcapsules assembled via layer‐by‐layer deposition of the natural polyphenol tannic acid and poly( N ‐vinylpyrrolidone) with 4 nm iron oxide nanoparticles incorporated in the capsule wall are introduced as efficient contrast‐enhanced imaging agents that combine magnetic resonance imaging with ultrasound‐triggered drug release for real‐time tracking and targeted delivery of anticancer therapeutics in vivo.